Let the brothers speak: African American men designing an inclusive learning paradigm that transforms an urban community college classroom culture - Sammie M. Dortch (Adult Education Research Conference, 1994)
Professor and learner collaboration through authentic discourse is a key to African American men discovering their "voice," and engaging in paradigm design that will increase the men's sense of inclusion in the urban community college culture. The future of the institution and of the workplace are linked to this process.